HUBUNGAN ANTARA LINGKUNGAN FISIK TERHADAP KEJADIAN DEMAM BERDARAH DENGUE KABUPATEN SLEMAN - Tika Pustika Fersari; Nur Afni Maftukhah; Zairinayati (Badan Perencanaan Pembangunan Daerah Kabupaten Sleman, 2026)
Dengue Hemorrhagic Fever (DHF) remains an important public health issue in Indonesia, including in Sleman Regency. The physical environment of the home actually plays a role in supporting the presence of Aedes aegypti mosquitoes, which can influence the incidence of DHF. This study aims to analyze the physical environmental factors that affect the incidence of DHF among the community in the working area of Gamping I Health Center, Sleman Regency. This research is an observational analytical quantitative study with a case-control design. The study sample consisted of 32 respondents, namely 8 in the case group and 24 in the control group, using purposive sampling technique. The variables studied included ventilated windows, humidity, and home lighting. Data were collected through observation using a checklist and analyzed with Fisher's Exact test at a 95% confidence level. The research results indicate that screened ventilation has a significant relationship with the incidence of dengue fever (p = 0.039; OR = 0.072). Residential lighting also shows a significant relationship with the incidence of dengue fever (p = 0.039; OR = 0.072). Meanwhile, household humidity does not show a significant relationship with the incidence of dengue fever (p = 0.642; OR = 0.347). This study concludes that screened ventilation and lighting are physical environmental determinants associated with the incidence of dengue fever in the community within the service area of Gamping I Health Center, Sleman Regency. Efforts to control dengue fever need to be directed at improving the physical conditions of homes through the installation of screens on ventilation and enhancement of household lighting as part of environmentally-based vector control.